Design of a 3D Top-Loaded Low-Profile Sleeve Antenna for UAV Applications - Lingsheng Yang; Ziling Xing; Shihao Xu; Dan Zhang; Yajie Li (IEEE Access, 2020)
In this article, a 3D top-loaded low profile sleeve antenna for unmanned aerial vehicle (UAV) applications is proposed. By loading a 3D disc cone structure on the top of a sleeve antenna, the overall height of the antenna can be significantly reduced compared with the height of a traditional quarter-wavelength monopole antenna. In addition, adding shorted columns between the top plate of the disc cone and the ground can generate a new resonant point at lower frequency, so that the frequency bandwidth can be effectively extended. Finally, in order to further achieve the miniaturization of the antenna, an annular slot ring structure was etched on the upper surface of the top plate. Under the conditions of S11 <; -10dB, the designed antenna with a total size of 160mm × 160mm × 26.6mm (0.44λ × 0.44λ × 0.07λ) has a wide band covering from 840MHz to 1.69GHz (67.2%), while the height of the proposed antenna is only 0.07λ (where λ is the wavelength of the lowest frequency point). Moreover, omnidirectional radiation performances through the operating band can be achieved for both the measured and simulated results.